Major and minor salivary gland cancers: A multicenter retrospective study - ARIKAN, RUKİYE; KÖSTEK, OSMAN (My University, 2023)
Background: Most of the studies on salivary gland cancers are limited for various reasons such as being single-center, small number of patients, including only major or minor SGCs, or only including epidemiological data. Methods: A total of 37 medical oncology clinics from different regions of Turkey participated in this retrospective-multicenter study. The analyzed data included clinical and demographical features, primary treatment, metastasis localizations, and treatments and includes certain pathologic features. Results: The study included data from a total of 443 SGCs. 56.7% was in major salivary glands and 43.3% was in minor salivary glands. Distant metastasis in the major SGCs was statistically significantly more common than in the minor SGCs, locoregional recurrence was statistically significantly more common in the minor SGCs than in the major SGCs (p = 0.003). Conclusions: Epidemiological information, metastasis and recurrence patterns, treatment modalities, and survival analysis of the patients over 20 years of follow-up are presented.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KULAK BURUN BOĞAZ; Clinical Medicine (MED); CLINICAL MEDICINE; OTORHINOLARYNGOLOGY; Otorhinolaryngology; histopathology; incidence; major salivary gland; minor salivary gland; salivary gland cancers; histopathology; incidence; major salivary gland; minor salivary gland; salivary gland cancers